Adaptive Leadership in the 2026 Curriculum Transformation at SDN Bono Magelang - Ina Nur Cahyani; Rahmat Mulyono; Jumintono (Universitas Pakuan, 2026)
The transformation of the 2026 National Curriculum requires adaptive leadership from school principals to implement deep learning, differentiated learning, coding, and compulsory English in elementary schools. This descriptive qualitative case study aims to analyze the role of the adaptive leadership of the principal of SDN Bono Magelang in facilitating adaptation to these changes, identifying the strategies implemented, and examining their impact on curriculum implementation. A purposive sample included the principal, three teachers from grades 3–6, and one parent representative, with data collected through semi-structured interviews, observations, and document analysis of the 2026 Curriculum Lesson Plans (RPP). Miles & Huberman thematic analysis was employed to process the data, supported by source triangulation. The results indicate that strategies of flexibility (hybrid training), collaboration (teacher-student-parent teams for deep learning projects), and technology integration (Google Classroom with hotspot subsidies) successfully reduced teacher resistance by 70%, increased lesson plan readiness by 90%, and improved student learning interest by 25%. Rural infrastructure challenges were addressed through a humanistic approach and incentives. In conclusion, adaptive leadership is essential for the successful implementation of the 2026 Curriculum in areas such as Grabag Magelang, with implications for a replication model for elementary schools in Central Java..